Catalysing change in health and medical research policy: an Australian case study of deliberative democracy to reform sex and gender policy recommendations - Haupt, Sue; Carcel, Cheryl; Halliday, Lily; Billiards, Saraid; Carson, Lyn; Redman, Kyle; Lappan-Newton, Scott; Aubrey, Karin R.; Bickendorf, Xander; Bourke, Jane E.; Buchert, Michael; Duarte, Jessica Da Gama; et al. (Frontiers in Public Health, 2025)
Revising public health policy based on new data does not happen automatically. This is acutely relevant to the now undeniable evidence that many diseases develop differently between the sexes and may also be affected by gender. Current health and medical practices across the globe generally fail to cater for sex and gender effects in common diseases. Inadequate policy frameworks to guide the comprehensive inclusion of sex and gender in research jeopardises scientific rigour and ultimately the practices they underpin. To ensure that Australian health and medical research is fit-for-purpose, we realised that potent initiatives would be necessary to expedite strategic reframing of thought and behaviour. Here we report on our innovative engagement of end-users for democratic self-determined policy reform to guide health and medical research, based on robust data. We draw upon our specific study to outline seven key steps that can be adopted to accelerate effective change, across a breadth of evidence-based initiatives to reform health policies.